(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Re-forensic examination is not only of great importance for forensic investigation bodies, but also for forensic examination is important in improving the quality of work. Appointment of re-examination is appointed only when a suspicion arises from the conclusion (examination) of the primary forensic expert during the investigative investigation. However, the suspicion is not always well-founded, in later times it is customary to appoint a re-examination by the investigation and inquiry authorities unilaterally, that is, when the victim or the suspect is dissatisfied with the initial conclusion.